Franz Schubert - Adlard, Henry, 1828-1869 (engraver):::Creator::::::::::::; Kriehuber, Joseph, 1800-1876 (lithographer):::Contributor:::::::::::: (England; London; Longmans and Co.)
Portrait engraving of Franz Schubert by Henry Adlard possibly based on the lithograph by Joseph Kriehuber.